Drehscheibe Graz Musikkulturelle Verbindungen im 19. Jahrhundert - Harer, Gudrun (Neue Beiträge zur Aufführungspraxis, 2022)
Mobility and networks are not just topical issues today. Graz's cultural life was already significantly influenced by these factors in the 19th century. This is illustrated by the research contributions published in this anthology, which are based on hitherto little-noticed manuscript sources, including diaries and journals.